Optimizing Sustainable Supply Chains: An Analysis of Quantity-Discount Pricing Strategies Under Carbon Cap-and-Trade Regulations - Xi-Bin Lin; Jonas Chao-Pen Yu; Kung-Jeng Wang; Hui-Ming Wee (Mathematics)
This study investigates two pricing strategies within a vendor-buyer supply chain system under cap-and-trade regulation, emphasizing demand sensitivity to market price and green technology investment. The findings reveal that quantity discounts significantly enhance profitability across the supply chain by encouraging buyers to place larger orders, thereby benefiting vendors, buyers, and end consumers. A novel profit-sharing parameter is introduced to foster sustainable and mutually beneficial relationships between supply chain participants. A search algorithm is developed to determine the optimal solutions by using the profit-sharing mechanisms. The analysis yields three key insights: first, a critical cap threshold is identified, enabling supply chain participants to make informed strategic decisions based on the value of the cap; second, another critical cap threshold is derived to assist governments in setting feasible emission limits that incentivize vendors to invest in green technology—caps below this threshold may discourage such investments; third, a reasonable return on investment (ROI) benchmark is established to guide vendors in adopting effective green technology strategies. Numerical examples and sensitivity analyses are conducted to illustrate the theoretical framework and validate the findings.